Implementación de la metodología croa en la creación de objetos de aprendizaje y su uso en un ambiente virtual de enseñanza-aprendizaje - Edwin Fabián, Morocho Mendoza (2021)
ABSTRACT At present, the demands of the knowledge society and the responsibility to offer the necessary training to students, the same that responds to the standards of educational quality. For this, the teacher resorts to the use of different methodologies to transmit information more appropriately. The main problem of this research work was the lack of use of a methodology for the creation of learning objects by teachers, whose general objective is manifested in the implementation of the CROA methodology, in the creation of learning objects and their use in virtual environments for teaching and learning in teachers of primary and high school of the Unidad Educativa “Daniel Enrique Proaño” in the city of Quito, in the parish of La Libertad, and the province of Pichincha. The research approach is qualitative; the level of research is exploratory, descriptive, and propositional. By the place, it is bibliographic and field research. In terms of time, it is transversal. It is also non-experimental. The techniques for data collection were the survey received through Google forms and as an instrument the questionnaire; the population consisted of 32 teachers of primary and high school, it worked with the whole population, from the results obtained, it is concluded that the implementation of the CROA methodology for the creation of learning objects and its use in a virtual teaching and learning environment using a didactic guide, contributes significantly to providing teachers with a viable mechanism in the field of design and creation and appropriate use of learning objects, allowing them to make appropriate decisions when creating educational materials such as learning objects through the proposal of a didactic guide for the implementation of the CROA methodology in the creation of learning objects and their use in a virtual teaching and learning environment. Keywords: CROA methodology, learning objects, virtual environments. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR C.C. 0603156258